2007
DOI: 10.1620/tjem.211.401
|View full text |Cite
|
Sign up to set email alerts
|

Facial Nerve Conduction after Sclerotherapy in Children with Facial Lymphatic Malformations: Report of Two Cases

Abstract: Surgical excision is thought to be the standard treatment of choice for lymphatic malformations. However, when the lesions are limited to the face only, surgical scar and facial nerve injury may impair cosmetics and facial expression. Sclerotherapy, an injection of a sclerosing agent directly through the skin into a lesion, is an alternative method. By evaluating facial nerve conduction, we observed the long-term effect of facial lymphatic malformations after intralesional injection of OK-432 and correlated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In 2 series with 128 cases and 21 cases, temporary palsy of the facial nerve following OK-432 sclerotherapy occurred in 2 patients and 1 patient, respectively [9,16]. Facial nerve conduction after sclerotherapy with OK-432 was evaluated by Lin et al [17] in only 2 patients, and nerve conduction and blink reflex were found normal in both.…”
Section: Discussionmentioning
confidence: 97%
“…In 2 series with 128 cases and 21 cases, temporary palsy of the facial nerve following OK-432 sclerotherapy occurred in 2 patients and 1 patient, respectively [9,16]. Facial nerve conduction after sclerotherapy with OK-432 was evaluated by Lin et al [17] in only 2 patients, and nerve conduction and blink reflex were found normal in both.…”
Section: Discussionmentioning
confidence: 97%
“…Ideally, the administered agents should be retained inside the lumens of the veins in the VM, and should not damage the surrounding healthy tissues. However, percutaneous sclerother-apy can sometimes cause serious functional and cosmetic sequelae, such as peripheral nerve disturbances [3,811], cutaneous necrosis [10,12] and detrimental effects on the muscle [13]. Of these, peripheral nerve disturbances, such as facial nerve paralysis or recurrent laryngeal nerve paralysis resulting in vocal cord paralysis, represent serious problems [9].…”
Section: Introductionmentioning
confidence: 99%